Dysfunctions, Molecular Mechanisms, and Therapeutic Strategies of Regulatory T Cells in Rheumatoid Arthritis - Li, Xiaoya; Xu, Huihui; Huang, Jing; Luo, Dan; Lv, Shuang; Lu, Xiangchen; Xiao, Cheng (Frontiers in Pharmacology, 2021)
Regulatory T cells (Tregs) represent a distinct subpopulation of CD4+ T lymphocytes that promote immune tolerance and maintain immune system homeostasis. The dysfunction of Tregs is tightly associated with rheumatoid arthritis (RA). Although the complex pathogenic processes of RA remain unclear, studies on Tregs in RA have achieved substantial progress not only in fundamental research but also in clinical application. This review discusses the current knowledge of the characterization, functions as well as molecular mechanisms of Tregs in the pathogenesis of RA, and potential therapies for these disorders are also involved.